2006
DOI: 10.1890/04-1957
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Herbivory and Bottom-Up El Niño Effects on Galápagos Rocky-Shore Communities

Abstract: We evaluated the effects of marine iguanas, sally lightfoot crabs, and fish on rocky‐shore sessile organisms at two sites at Santa Cruz Island, Galápagos Islands, Ecuador, for 3–5 years during and after the 1997–1998 El Niño, using exclusion cages to separate the effects. Plots exposed to natural grazing were dominated either by encrusting algae or by red algal turf and articulated corallines. Algae fluctuated in response to El Niño in the following way. During an early phase, crustose Gymnogongrus and/or red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 48 publications
9
105
1
9
Order By: Relevance
“…This high susceptibility to herbivory has been usually associated with the lower biomass of ephemeral macroalgae observed on many temperate shores (Coleman et al, 2006;Hawkins, 1981;Nielsen and Navarrete, 2004;Poore et al, 2012;Steneck and Dethier, 1994) and on a few tropical intertidal shores as well (Kennish et al, 1996;Menge et al, 1985;Vinueza et al, 2006). However, the extent to which grazers control algal biomass may vary substantially at different spatial scales, even within the same shoreline, independently of the general climatic region (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high susceptibility to herbivory has been usually associated with the lower biomass of ephemeral macroalgae observed on many temperate shores (Coleman et al, 2006;Hawkins, 1981;Nielsen and Navarrete, 2004;Poore et al, 2012;Steneck and Dethier, 1994) and on a few tropical intertidal shores as well (Kennish et al, 1996;Menge et al, 1985;Vinueza et al, 2006). However, the extent to which grazers control algal biomass may vary substantially at different spatial scales, even within the same shoreline, independently of the general climatic region (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Algal blooms at the lower intertidal zone on Hong Kong shores extend longer into the summer, probably because of reduced heat stress at this level (Williams, 1993). In many cases, however, the effect of seasonal intensification of heat stress can be confounded with variation in nutrient supply, especially in nutrient-poor waters (Vinueza et al, 2006). Ormond and Banaimoon (1994) showed that macroalgal abundance peaked during late summer and autumn at intertidal rocky shores along the Hadramout Coast, southern Yemen, coinciding to the seasonal upwelling of nutrient-rich waters and not with air temperature minima.…”
Section: Introductionmentioning
confidence: 99%
“…Herbivores can inXuence the structure of benthic algal communities through the consumption of large amounts of algal biomass (Lubchenco and Gaines 1981;Carpenter 1986;Vinueza et al 2006;Jormalainen and Honkanen 2008). In response to this herbivore pressure, macroalgae have developed diVerent strategies, one of which is the defense of tissues in ways that makes them less palatable for potential consumers (reviewed in DuVy and Hay 1990;Cronin 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Reports (Vinueza et al 2006) of crabs such as the sally light-foot crabs (G. grapsus) in the Galapagos show preference to red algal turfs and Ulva and some amounts of filamentous greens but these crabs avoided encrusting algae, including filamentous brown algae.…”
Section: B46mentioning
confidence: 99%